Accounting and economic decision - Grace, E. A. (Statistical and Social Inquiry Society of Ireland, 1953)
Accounts, whether prepared for shareholders or management, provide a systematic basis for determining the employment of a very large part of national resources of manpower, material and technique. I conceive that an attempt to examine the underlying methods and their application may be of interest to students of social sciences for whom this Society is a meeting place. I might have hesitated to address you on so traditionally simple a subject as double-entry book-keeping, but recent statements of accountants and economists have emphasised that the significance of the methods employed is not sufficiently appreciated and that there is by no means unanimity on the efficacy of some of the most fundamental traditional assumptions.
Read before the Society, 27 March 1953
Keywords: Accounting in Ireland; Economic decision making; Accounting methods; 314.15